Monograph Review Kucher A.V. " Strategic directions of the development of low carbon land use to strengthen resilience to climate change" - Baliuk, S. A. (Man and Environment. Issues of Neoecology, 2020)
The presented monograph is a relevant and thorough completed scientific work based on modern theoretical developments, economic and mathematical processing of empirical data, comprehensive analysis and generalization of the best domestic and foreign experience on the problem of adaptation of agricultural land use to climate change. The monograph can be useful for politicians, scientists, practitioners, researchers and educators, higher education seekers and anyone interested in environmental and economic issues of low-carbon agricultural land use.